Adaptive management of an environmental watering event to enhance native fish spawning and recruitment - King, A. J.; Ward, K. A.; O’connor, P.; Green, D.; Tonkin, Z.; Mahoney, J. (Freshwater Biology, 2010)
1. A common goal of many environmental flow regimes is to maintain and/or enhance the river’s native fish community by increasing the occurrence of successful spawning and recruitment events. However, our understanding of the flow requirements of the early life history of fish is often limited, and hence predicting their response to specific managed flow events is difficult. To overcome this uncertainty requires the use of adaptive management principles in the design, implementation, monitoring and adjustment of environmental flow regimes. 2. The Barmah-Millewa Forest, a large river red gum forest on the Murray River floodplain, south-east Australia, contains a wide variety of ephemeral and permanent aquatic habitats suitable for fish. Flow regulation of the Murray River has significantly altered the natural flood regime of the Forest. In an attempt to alleviate some of the effects of river regulation, the Forest’s water regime is highly managed using a variety of flow control structures and also receives targeted Environmental Water Allocations (EWA). In 2005, the largest environmental flow allocated to date in Australia was delivered at the Forest. 3. This study describes the adaptive management approach employed during the delivery of the 2005 EWA, which successfully achieved multiple ecological goals including enhanced native fish spawning and recruitment. Intensive monitoring of fish spawning and recruitment provided invaluable real-time and ongoing management input for optimising the delivery of environmental water to maximise ecological benefits at Barmah-Millewa Forest and other similar wetlands in the Murray-Darling Basin. 4. We discuss possible scenarios for the future application of environmental water and the need for environmental flow events and regimes to be conducted as rigorous, large-scale experiments within an adaptive management framework.
Keywords: floodplain river; regulated flows